Pengaruh Hutang Jangka Pendek dan Hutang Jangka Panjang Terhadap Profitabilitas pada PT Unilever Indonesia Tbk - Nurdiana; Sissah; M.Yunus (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Payables are obligations that must be made to other parties in the form of currency, goods or services in the future, the impact of payments that have occured in the future, and the impact of transaction that arise in the destiny. Based on the repayment period, debt can be divided into two, namely brief-time period debt and lengthy-time period. This observe tergets to decide the impact of brief-time period and long-time period on profitability at PT Unilever Indonesia Tbk. This studies is a quantitative studies. The analvtical method used is a couple of linear regression. The end result of this observe suggest that short-term and long-term has a negative and significant imfact on profitability.